Laryngeal Inflammation in the Sudden Infant Death Syndrome - K. Scadding, Glenis; Brock, Christine; Chouiali, Fazila; Hamid, Qutayaba (Current Pediatric Reviews, 2014)
Abstract: Objective: Sudden infant death syndrome (SIDS) is marked by ’the sudden death of an infant that is unexpected by history and remains unexplained after a thorough forensic autopsy and a detailed death scene investigation’. The cause is unknown. Excessive subglottic submucosal glandular tissue and excessive sulphated mucus glycoprotein in the larynges of SIDS babies have been previously reported from our institution. We now report on laryngeal immunohistology. Methods: Larynges from 7 children who died from Sudden Infant Death Syndrome (SIDS) at under 16 weeks of age were examined immunohistologically and compared to those from 8 age- matched control infants who died from other causes. Results: The SIDS babies had increased inflammatory changes in the laryngeal epithelium and sub- epithelium with raised numbers of cells staining for elastase (p<;0.01), EG2(a marker for activated eosinophils) (p<0.01) and CD4(p<0.05) suggesting that some SIDS deaths involve preceding inflammation. Conclusions: Although death may be sudden and unexpected it appears that, at least in some SIDS victims, there is a preceding inflammatory process in the larynx which may allow hyper-reactivity of laryngeal reflexes and consequent apnoea. This observation concurs with others in the SIDS literature and offers a field for further research and possible prevention.
Keywords: larynx